Using chloroprocaine for spinal anaesthesia in outpatient knee-arthroscopy results in earlier discharge and improved operating room efficiency compared to mepivacaine and prilocaine - Gebhardt, Volker; Hausen, Sebastian; Weiß, Christel; Schmittner, Marc (Knee surgery, sports traumatology, arthroscopy, 2019)
PurposeKnee arthroscopies are regularly carried out in an outpatient setting. The purpose of this retrospective analysis was to investigate the impact of different local anaesthetics for spinal anaesthesia on operating room efficiency (perioperative process times) and postoperative recovery. This study aims to determine the optimal LA for SPA in patients undergoing knee arthroscopy at a day-surgery centre.MethodsAnaesthesia records of all patients undergoing knee arthroscopy under spinal anaesthesia from 2010 until 2017 were analysed. Patients were categorised as having received spinal anaesthesia with prilocaine, mepivacaine or chloroprocaine.ResultsThree-hundred and nine patients were included. Postoperative recovery was significantly faster for chloroprocaine 1% compared with both other local anaesthetics regarding all stages of recovery until discharge. Perioperative processes and surgery time were significantly shorter when chloroprocaine was used. Early postoperative pain occurred more frequently and earlier after spinal anaesthesia with chloroprocaine. Nevertheless, pain intensity did not differ between groups.ConclusionSpinal anaesthesia provides reliable blocks for outpatient knee arthroscopy. Considerations on the choice of local anaesthetic for spinal anaesthesia must include not only the recovery profile, but also the impact on operating room efficiency. Due to a superior recovery profile, low incidences of adverse side effects and raised operating room efficiency, chloroprocaine is the recommendable local anaesthetic for spinal anaesthesia in patients undergoing knee arthroscopy in an ambulatory setting. Since the frequency of SPA in patients undergoing outpatient knee arthroscopy is rising yearly, the results of this study are of high clinical relevance. The use of chloroprocaine leads to improved recovery, optimized perioperative processes and consecutively to a raised OR efficiency.Level of evidenceIII.